Granulomatous meningoencephalitis due to Halicephalobus gingivalis in a horse - Sant’Ana, Fabiano J. F. de; Ferreira Júnior, Jair A.; Costa, Yara L. da; Resende, Rosely M. de; Barros, Claudio S. L. (Brazilian Journal of Veterinary Pathology, 2012)
A 6-year-old, male, mixed-breed horse was presented for necropsy with history of blindness, ataxia, incoordination, peddling movements, nystagmus, depression, muscle spasms, abnormal appetite, mydriasis, abnormal behavior, and recumbency. There were no gross findings in the brain. Microscopically, there was meningoencephalitis characterized by a mild to moderate multifocal granulomatous inflammatory reaction, affecting mainly the cerebellum and, with lesser intensity, the thalamus and brain stem. Intralesional larval nematodes with morphology consistent with Halicephalobus gingivalis were observed. Based on the histopathological findings, a diagnosis of granulomatous meningoencephalitis by H. gingivalis was made.